The Development of an Aftermarket Intercooler Spray for Turbocharged Vehicles using Water - Muhammad Izzat Nor, Ma'arof; Sathurshan, Suresh; Shaheerthana, Suresh; Yuli Panca, Asmara; Girma, Tadesse Chala (INTI International University, 2019)
An intercooler is a type of heat exchanger used to cool the air which has been compressed by turbocharger. The temperature at the intercooler increases as more compressed hot air enters from the turbocharger. Factors such as engine heat and weather condition hinder the efficiency and power output. The objective of this study was to design and develop an intercooler cooling system operating autonomously. This system senses temperature changes at the intercooler and spray water or any diluted solution with varying enthalpy of vaporization and thermal capacity over the intercooler when the outlet temperature is high. The system developed was powered by Arduino Uno microcontroller that gathers data from the temperature sensor and triggers the spraying mechanism when required automatically. The results show that spray cooling had significant impact as the efficiency improved from 56.52% to an outstanding efficiency of 89.70% by spraying tap water. Even the lowest possible efficiency of an intercooler with the combination of spray mechanism was 87.69% using distilled water, which was over 50% more efficient than the ordinary intercooler without the spray cooling unit. Conclusively, this newly designed portable plug-and-play intercooler spray unit would be beneficial in increasing the performance of the intercooler by improving the heat exchange capacity of the unit. For future studies, other types of solutions could be investigated as the intercooler spray.